Survival of Adjuvant Drugs for Treatment of Pemphigus: A Population-based Cohort Study - Khalaf Kridin; Christoph M. Hammers; Ralf J. Ludwig; Dana Tzur Bitan; Arnon D. Cohen (Medical Journals Sweden, 2021)
Drug survival reflects the real-life efficacy and safety of therapeutic agents. Evidence regarding the durability of adjuvant agents in the treatment of pemphigus is sparse. The aims of this study were to investigate the survival of adjuvant agents used to manage patients with pemphigus, and to identify predictors of treatment dropout. A retrospective population-based cohort study was designed to follow patients with pemphigus managed by adjuvant agents. The study population included 436 patients with pemphigus managed by 608 adjuvant agent courses. The highest median drug survival time was observed for rituximab (43.6 months, 95% confidence interval (95% CI) 5.3-81.9), followed by cyclophosphamide (30.5 months; 95% CI 10.5-50.5), azathioprine (22.9 months; 95% CI 15.6-30.2), and mycophenolate mofetil (20.2 months; 95% CI 10.0-30.4). Compared with azathioprine, cyclosporine (adjusted hazard ratio 2.98; 95% CI 1.57-5.62; p = 0.005) and dapsone (adjusted hazard ratio 1.83; 95% CI 1.07-3.15; p = 0.027) were associated with a significantly increased risk of drug discontinuation. To conclude, rituximab, azathioprine, and mycophenolate mofetil demonstrated better durability, whilst dapsone and cyclosporine were associated with low drug survival and high dropout.